Evaluasi pengembangan desa wisata, studi kasus pada desa wisata Pacarejo Gunungkidul - Thea Monika; Aditha Agung Prakoso (Journal of Tourism and Economic, 2023)
Tourism villages are currently the government's flagship program through the tourism sector that can encourage the development of post-pandemic tourism, this is due to the nature of tourism villages that can provide direct benefits to local and surrounding communities. The dynamic development of tourism also provides challenges in the development of tourist villages, so evaluation is needed as one of the strategies in village management. This research aims to evaluate the condition of Pacarejo Tourism Village using a qualitative descriptive method based on the theory of tourism villages, so that it can provide the proper strategies in determining guidelines and strategies for future development as an Independent Tourism Village based on local values.